2016
DOI: 10.1016/j.neurobiolaging.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

APOE and aging-related cognitive change in a longitudinal cohort of men

Abstract: a b s t r a c tWe examined associations between APOE major isoforms, rs405509 promoter and rs440446 intron-1 polymorphisms, and nonpathologic cognitive aging. Men from the Helsinki Birth Cohort Study took the Finnish Defence Forces Basic Intellectual Ability Test twice, at age 20.1 (n ¼ 404) and 67.6 years (n ¼ 247). APOE major isoforms did not associate with cognitive ability. In the APOE major isoform-adjusted analyses, the number of rs405509 minor alleles was associated with a higher cognitive ability total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The double homozygous genotype (rs405509 TT/ε4ε4) exhibited a significant reduction in general cognition, memory, and attention [68]. However, in a recent study that included elderly men from Finland, researchers found that the rs405509 TT genotype was significantly associated with improved general cognition, language, arithmetic, and visual spatial ability, independent of the APOE major isoforms [69]. This likely indicates that the effects of rs405509 are different among different ethnicities.…”
Section: The Effects Of the Apoe Gene On Cognitive Function And Dementioning
confidence: 99%
“…The double homozygous genotype (rs405509 TT/ε4ε4) exhibited a significant reduction in general cognition, memory, and attention [68]. However, in a recent study that included elderly men from Finland, researchers found that the rs405509 TT genotype was significantly associated with improved general cognition, language, arithmetic, and visual spatial ability, independent of the APOE major isoforms [69]. This likely indicates that the effects of rs405509 are different among different ethnicities.…”
Section: The Effects Of the Apoe Gene On Cognitive Function And Dementioning
confidence: 99%
“…12,15 Test scores have been associated with, for example, cardiovascular disease and stroke risk 16 and APOE polymorphisms. 17 For all analyses, the cognitive ability test scores were converted to IQ-type scores with mean 100 and SD 15.…”
Section: Standard Protocol Approvals Registrations and Patient Consmentioning
confidence: 99%
“…APOE promoter polymorphisms are closely related to aging and may have independent mechanisms for normal aging and pathological aging (Rantalainen et al, 2016 , 2019 ). As we found in our study, the results of linear regression analysis showed that the interaction between the rs405509 genotype and age had a significant effect on general cognitive performance and execution function scores.…”
Section: Discussionmentioning
confidence: 99%